Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1521/suli.35.2.217.62880
|View full text |Cite
|
Sign up to set email alerts
|

Historical Change of Suicide Seasonality in the Canton of Zurich, Switzerland

Abstract: Current research is yielding an increasingly heterogeneous picture of suicide seasonalities: They seem to depend on methods and, moreover, they seem to have smoothed in recent decades. This work examines the latter issue by comparing suicide seasonalities in the canton of Zurich, Switzerland, in the 16 th -18 th centuries, 1901-1920 and 1969-94. The results indicate shifts of peaks and lows on suicide seasonalities over the centuries, with a smoothing of seasonalities toward the 21 th century. The recent perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
2
Order By: Relevance
“…There are also certain studies that did not confirm seasonal variation (19,41,44,47,51,56,61). It is noteworthy that longterm studies have shown that in some countries, the pre-existing seasonal variation tends to diminish or vanish with time (18,19,20,51,59,86,90). It is crucial to underline that the results regarding the evaluation of seasonality depend on the method used for the evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also certain studies that did not confirm seasonal variation (19,41,44,47,51,56,61). It is noteworthy that longterm studies have shown that in some countries, the pre-existing seasonal variation tends to diminish or vanish with time (18,19,20,51,59,86,90). It is crucial to underline that the results regarding the evaluation of seasonality depend on the method used for the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing data from Switzerland, a continuous weakening of the seasonal variation has been observed. Despite this weakening, there is still a seasonal variation in violent suicides during spring, mainly in rural regions, especially in suicides by hanging and drowning (20,38,59). Also in a study conducted in Hungary, seasonality during summer is associated with suicides by poisoning, hanging, and jumping (60).…”
Section: Factors Affecting Suicide Seasonality: Age and Methods Of Suimentioning
confidence: 99%
“…In some cantons like Zurich, the seasonality has disappeared even in hanging and drowning suicides. 32 However, in other cantons hanging and drowning suicides are still important sources of seasonal variation, such that the decreasing importance of these suicide methods-with an overall proportion of 62% in 1881-1920 but only 35% in 1969-2000-has accentuated the smoothing process in the overall data.…”
Section: Approach (A)mentioning
confidence: 99%
“…The findings are consistent when using a standardized method of data collection and minimizing the various influential factors by using region-specific meteorological data. The short distance between the site of suicide and the place of environmental measurement of the meteorological parameters, such as air temperature and global radiation, corrects the methodological deficits of previous studies, which examined larger geographical regions with the risk of potential geographical bias (Ajdacic-Gross et al, 2005;Bambrick et al, 2011;Brown et al, 2010;Christodoulou et al, 2009;Hanninen et al, 2011;Kordic et al, 2010;Lester et al, 1990Lester et al, , 2001. In these previous investigations, the macrometeorological values of the entire countries or regions might not be accurately representative of the local microenvironment where the acts took place.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the seasonal dependency and asymmetry remains unclear (Ajdacic-Gross et al, 2005, 2010. Previous research has investigated typical influences, for example, meteorological (such as global warming), psychiatric comorbidities, method of suicide ("violent" vs. "nonviolent"), and sex-and age-associated factors (Biermann et al, 2009;Deisenhammer, 2003;Likhvar et al, 2011;Marusic, 2005;Preti et al, 2000Preti et al, , 2007Retamal et al, 1998;Scribante et al, 2004).…”
Section: Introductionmentioning
confidence: 99%